KARAKTERISTIK IBU PASANGAN USIA SUBUR YANG MENGALAMI ABORTUS DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2010 – 2013 - erniwati silalahi; Sori Muda Sarumpaet; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABTRACTS Abortion is an important public health problem. It gives impact the maternal morbidity and mortality in the cases of bleeding complications and sepsis. In the world, there are 114 cases of abortion per hour and in 2010 about 4% of maternal mortality in Indonesia. This study is to know the characteristicsmother of Eligible couples in Santa Elisabeth hospital Medan in 2010-2013, this study used a descriptive study with case series design. Population and sample is the whole Mother of Eligible couples 106 people. The highest proportion of the age group 28-31 years is 32,1%, Bataknese 85,5%, Protestant christian 59,4%, housewife 40,6%, Medan 83,0%, bleeding 70,7%, the first trimester 91,5%, no history of abortion 84,9%, unsafe parity 72,4%, spontaneous abortion 99,1%, incompletus abortion 77,4%, no complications 95,3%, no history of diseases 79,2%, curettage 78,3%, not referral 55,7%, the average duration of patient care is 2 days, a status while returning cured97,2%, and own costs 80,2%. There is no difference between proportion ofparity based on history of abortion (p= 0,274),parity based oncomplications(p= 0,320), complication based on circumstances after treatment (p= 1.000), medical management by circumstances after treatment (p= 0,118),duration of treatment by the complication (0,145), duration of treatment by the history of diseases (p=0,066), and motherof Eligible couples having abortion with the conservative medical treatment, the average duration of treatment was significantly higher than curettage (3 days vs 2 day; t=-4,049, p=0,000). Santa Elisabeth hospital expected to complete the record of status card on the history of prenatal care.Itis expected to the society by the preventingthe abortion by improving family planning and to related health servicesto do counseling to the mother of Eligible couples who experience of abortion on the prevention in subsequent pregnancies. Keyword: characteristics, Abortion of Eligible Couples, Santa Elisabeth Hospital